2020
DOI: 10.1021/acs.nanolett.0c01176
|View full text |Cite|
|
Sign up to set email alerts
|

Exchange Bias Effect in Ferro-/Antiferromagnetic van der Waals Heterostructures

Abstract: The recent discovery of magnetic van der Waals (vdW) materials provides a platform to answer fundamental questions on the two-dimensional (2D) limit of magnetic phenomena and applications. An important question in magnetism is the ultimate limit of the antiferromagnetic layer thickness in ferromagnetic (FM)/antiferromagnetic (AFM) heterostructures to observe the exchange bias (EB) effect, of which origin has been subject to a long-standing debate. Here, we report that the EB effect is maintained down to the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…While for states 2 and 4, the orientation of some of the domains in FGT are parallel to the external magnetic field, while others are fixed to the domains in FPS due to the pinning effects caused by the proximity coupling, resulting in an inflexion in MOKE signal. Different from the single‐shifted hysteresis loop observed in FGT/FPS and FGT/CrPS 3 systems, [ 38 ] the curve here shows double‐shifted hysteresis loops, which is a clear evidence of exchange bias effects. This phenomenon is common and usually observed in the zero‐field cooled curves taken from AFM/FM systems where the T C of FM is higher than T N of AFM.…”
Section: Figurecontrasting
confidence: 91%
“…While for states 2 and 4, the orientation of some of the domains in FGT are parallel to the external magnetic field, while others are fixed to the domains in FPS due to the pinning effects caused by the proximity coupling, resulting in an inflexion in MOKE signal. Different from the single‐shifted hysteresis loop observed in FGT/FPS and FGT/CrPS 3 systems, [ 38 ] the curve here shows double‐shifted hysteresis loops, which is a clear evidence of exchange bias effects. This phenomenon is common and usually observed in the zero‐field cooled curves taken from AFM/FM systems where the T C of FM is higher than T N of AFM.…”
Section: Figurecontrasting
confidence: 91%
“…When assembling AFMs and ferromagnets in heterostructures, exchange bias is induced via exchange coupling. [ 160 , 161 , 162 ] Such an exchange coupling can be tuned by the gate voltage in vdW AFM/FM heterostructures. [ 161 ] This structure is useful in realizing efficient SOT devices, for instance, providing in‐plane exchange bias for SOT switching PMA magnets.…”
Section: Van Der Waals Ferromagnets and Antiferromagnets For Spin‐orbit Torquementioning
confidence: 99%
“…[ 160 , 161 , 162 ] Such an exchange coupling can be tuned by the gate voltage in vdW AFM/FM heterostructures. [ 161 ] This structure is useful in realizing efficient SOT devices, for instance, providing in‐plane exchange bias for SOT switching PMA magnets. Moreover, proximity‐coupling also plays an important role in these artificial structures.…”
Section: Van Der Waals Ferromagnets and Antiferromagnets For Spin‐orbit Torquementioning
confidence: 99%
“…Exchange bias (EB) has been extensively studied because of its applications in magnetic recording, giant magnetoresistance, and spin-valve devices since the first discovery of EB in Co–CoO nanoparticles by Meiklejohn and Bean in 1956 . EB is identified by a shift in magnetic hysteresis loop along the external field direction in a system with an interface of ferromagnetic (FM)–antiferromagnetic (AFM), , FM-spin glass (SG), , or FM-SG-AFM , after field cooling through the Neel temperature of the AFM or glass temperature of the SG. Conventionally, EB requires prebias of the interface moment via field cooling (FC) from a higher temperature to obtain FM unidirectional anisotropy. , In contrast to conventional field-cooled exchange bias, recent reports have shown that zero-field-cooled EB (ZEB) can also be obtained in some bulk alloys, , oxides, , and antiperovskite compounds systems, , where there is no need of an external field during cooling to induce unidirectional anisotropy. It is the complex magnetic states such as the coexistence of FM, AFM, and SG phases and the SG order in these systems that plays a crucial role in obtaining the ZEB effect. Compared to field-cooled EB, ZEB consumes less energy since no external field is needed during the cooling process, thus benefiting the device miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange bias (EB) has been extensively studied because of its applications in magnetic recording, giant magnetoresistance, and spin-valve devices since the first discovery of EB in Co− CoO nanoparticles by Meiklejohn and Bean in 1956. 1 EB is identified by a shift in magnetic hysteresis loop along the external field direction in a system with an interface of ferromagnetic (FM)−antiferromagnetic (AFM), 2,3 FM-spin glass (SG), 4,5 or FM-SG-AFM 6,7 after field cooling through the Neel temperature of the AFM or glass temperature of the SG. 4−7 Conventionally, EB requires prebias of the interface moment via field cooling (FC) from a higher temperature to obtain FM unidirectional anisotropy.…”
Section: Introductionmentioning
confidence: 99%